An uncommon abdominal fistula: Colonic diverticular disease complicated with colocutaneous fistula - Mesina, Cristian; Dumitrescu, Theodor Viorel; Calota, Firmilian; Daniela, Ciobanu (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Mesina C, Dumitrescu TV, Calota F, Daniela C. An uncommon abdominal fistula: colonic diverticular disease complicated with colocutaneous fistula. Turk J Gastroenterol 2018; 29: 248-9.